6.7 KiB
A derivative can be used to describe the rate of change at a single point, or the instantaneous velocity.
The formula used to calculate the average rate of change looks like this:
\dfrac{f(b) - f(a)}{b - a}
Interpreting it, this can be described as the change in y
over the change in x
.
- Speed is always positive
- Velocity is directional
As the distance between the two points a
and b
grow smaller, we get closer and closer to the instantaneous velocity of a point. Limits are suited to describing the behavior of a function as it approaches a point.
If we have the coordinate pair (a, f(a))
, and the value h
is the distance between a
and another x
value, the coordinates of that point can be described as ((a + h, f(a + h))
. With this info:
- The slope of the secant line can be described as
\dfrac{f(a + h) - f(a)}{a + h - a}
, which simplifies to\dfrac{f(a + h) - f(a)}{h}
. - The slope of the tangent line or the instantaneous velocity can be found by taking the limit of the above function as the distance (
h
) approaches zero:
\lim_{h \to 0}\dfrac{f(a + h) - f(a)}{h}
The above formula can be used to find the derivative. This may also be referred to as the instantaneous velocity, or the instantaneous rate of change.
Point Slope Formula (Review)
y - y_1 = m(x-x_1)
Given that m = f'(a)
and that (x_1, y_1) = (a, f(a))
, you get the equation:
y - f(a) = f'(a)(x - a)
Line Types
Secant Line
A Secant Line connects two points on a graph.
A Tangent Line represents the rate of change or slope at a single point on the graph.
Notation
Given the equation y = f(x)
, the following are all notations used to represent the derivative of f
at x
:
f'(x)
\dfrac{d}{dx}f(x)
y'
\dfrac{dy}{dx}
\dfrac{df}{dx}
- "Derivative of
f
with respect to $x$"
Functions that are not differentiable at a given point
- Where a function is not defined
- Where a sharp turn takes place
- If the slope of the tangent line is vertical
Higher Order Derivatives
- Take the derivative of a derivative
Constant Rule
The derivative of a constant is always zero.
\dfrac{d}{dx}[c] = 0
For example, the derivative of the equation f(x) = 3
is 0
.
Derivative of x
The derivative of x
is one.
For example, the derivative of the equation f(x) = x
is 1
, and the derivative of the equation f(x) = 3x
is 3
.
Exponential Derivative Formula
Using the definition of a derivative to determine the derivative of f(x) = x^n
, where n
is any natural number.
f'(x) = \lim_{h \to 0} \dfrac{(x + h)^n - x^n}{h}
- Using pascal's triangle, we can approximate
(x + h)^n
1
1 1
1 2 1
1 3 3 1
1 4 6 4 1
- Where
n = 0
:(x + h)^0 = 1
- Where
n = 1
:(x +h)^1 = 1x + 1h
- Where
n = 2
:(x +h)^2 = x^2 + 2xh + h^2
- Where
n = 3
:(x + h)^3 = 1x^3h^0 + 3x^2h^1 + 3x^1h^2 + 1x^0h^3 = 1x^3 + 3x^2h + 3xh^2 + 1h^3
Note that the coefficient follows the associated level of Pascal's Triangle (1 3 3 1
), and $x$'s power decrements, while $h$'s power increments. The coefficients of each pair will always add up to n
. Eg, 3 + 0
, 2 + 1
, 1 + 2
, and so on. The second term in the polynomial created will have a coefficient of n
.
\dfrac{(x + h)^n - x^n}{h} = \lim_{h \to 0} \dfrac{(x^n + nx^{n-1}h + P_{n3}x^{n-2}h^2 + \cdots + h^n)-x^n}{h}
P
denotes some coefficient found using Pascal's triangle.
x^n
cancels out, and then h
can be factored out of the binomial series.
This leaves us with:
\lim_{h \to 0} nx^{n-1} + P_{n3} x^{n-2}*0 \cdots v * 0
The zeros leave us with:
f(x) = n, \space f'(x) = nx^{n-1}
Sum and Difference Rules
\dfrac{d}{dx}(f(x) \pm g(x)) = f'(x) \pm g'(x)
Product Rule
\dfrac{d}{dx} (f(x) * g(x)) = \lim_{h \to 0} \dfrac{f(x +h) * g(x + h) - f(x)g(x)}{h}
This is done by adding a value equivalent to zero to the numerator (f(x + h)g(x) - f(x + h)g(x)
):
\dfrac{d}{dx} (f(x) * g(x)) = \lim_{h \to 0} \dfrac{f(x +h) * g(x + h) + f(x + h)g(x) - f(x+h)g(x) - f(x)g(x)}{h}
From here you can factor out f(x + h)
from the first two terms, and a g(x)
from the next two terms.
Then break into two different fractions:
\lim_{h \to 0} \dfrac{f(x + h)}{1} * \dfrac{(g(x + h) - g(x))}{h)} + \dfrac{g(x)}{1} *\dfrac{f(x + h) - f(x)}{h}
From here, you can take the limit of each fraction, therefore showing that to find the derivative of two values multiplied together, you can use the formula:
\dfrac{d}{dx}(f(x) * g(x)) = f(x) * g'(x) + f'(x)*g(x)
Constant Multiple Rule
\dfrac{d}{dx}[c*f(x)] = c * f'(x)
Quotient Rule
\dfrac{d}{dx}(\dfrac{f(x)}{g(x)}) = \dfrac{f'(x)g(x) -f(x)g'(x)}{(g(x))^2}
Exponential Rule
\dfrac{d}{dx} e^x = e^x
\dfrac{d}{dx}a^x = a^x*(\ln(a))
for all a > 0
Chain Rule
\dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x)
Examples
Given the function
(x^2+3)^4
, find the derivative.
Using the chain rule, the above function might be described as f(g(x))
, where f(x) = x^4
, and g(x) = x^2 + 3)
.
- First find the derivative of the outside function function (
f(x) = x^4
):
\dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...
- Multiply that by the derivative of the inside function,
g(x)
, orx^2 + 3
.
\dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)
Apply the chain rule to
x^4
If we treat the above as a function along the lines of f(x) = (x)^4
, and g(x) = x
, then the chain rule can be used like so:
4(x)^3 * x
Trig Functions
\lim_{x \to 0} \dfrac{\sin x}{x} = 1
\lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0
Sine
f'(x) = \lim_{h \to 0} \dfrac{\sin(x + h) - sin(x)}{h}
Using the sum trig identity, \sin(x + h)
can be rewritten as \sin x \cos h + \cos x \sin h
.
This allows us to simplify, ultimately leading to:
\dfrac{d}{dx} \sin x = \cos x
Cosine
\dfrac{d}{dx} \cos x = -\sin x
Tangent
\dfrac{d}{dx} \tan x = \sec^2x
Secant
\dfrac{d}{dx} \sec x = \sec x * \tan x
Cosecant
\dfrac{d}{dx} \csc x = -\csc x \cot x
Cotangent
\dfrac{d}{dx} \cot x = -\csc^2 x
Implicit Differentiation
- There's a reason differentials are written like a fraction
\dfrac{d}{dx} x^2 = \dfrac{d(x^2)}{dx}
, or, "the derivative ofx^2
with respect to $x$"\dfrac{d}{dx} x = \dfrac{dx}{dx} = 1
: The derivative ofx
with respect tox
is one\dfrac{d}{dx} y = \dfrac{dy}{dx} = y'
- Given the equation
y = x^2
,\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x
.
Examples
Differentiate
f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}
f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}
= 4x^\frac{1}{3} - x^{-6}
f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})
= 4x^{-2-\frac{2}{3}} + 6x^{-7}
= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}